Age as Adventure: Restorying Later Life - Randall, William (Narrative Works, 2022)
For many people, aging is perceived and experienced in implicitly tragic terms: as a narrative of decline, as little more than a downward trajectory toward decrepitude and death. Such a way of storying later life can set us up for (among other things) narrative foreclosure, which can fuel the mild-to-moderate depression to which older adults are susceptible in the face of aging’s many challenges. Insofar as our experience of aging is inseparable from our story of aging, this paper argues for an alternative narrative of later life. Drawing on concepts from narrative gerontology and narrative psychology, it outlines how later life can be re-genre-ated from tragedy to adventure in at least four inter-related directions: Outward, Inward, Backward, and Forward.